Polyurethane Treated in Ar/C2H2/Ar Plasma: Towards Deformable Coating with Improved Albumin Adsorption - Ilya A. Morozov (MDPI AG, 2021)
Plasma modification of soft polymeric surfaces has many prospects in creating biomedical devices. The deformability of the obtained coatings should be studied, as the usage of such materials implies mechanical loads. Polyurethane (a two-phase synthetic polymer) treated in argon/acetylene plasma, with post-treatment in argon plasma, was investigated. A carbon-containing nanocoating (discontinuous mesh-like structures) with structural–mechanical inhomogeneities is formed by the action of Ar/C2H2 plasma. The heterogeneities of the coating are due to the complex structure of the initial substrate and short duration of treatment; as the treatment time increases, the coatings become homogeneous, but their stiffness rises. The treated surfaces in the uniaxial tensile state have micro and/or nanocracks in certain cases of plasma treatment. This is associated with an increased elastic modulus of the coatings. The coatings without cracks have regions with sufficiently alternating stiffness. Post-treatment in argon plasma increases wettability and free surface energy, positively affecting the adsorption of albumin. The stiffness of such coatings increases, becoming more homogeneous, which slightly reduces their crack resistance. Thus, plasma coatings on soft polymers operating under mechanical loads without causing damage should have sufficiently low stiffness, and/or structural-mechanical heterogeneities that provide redistribution of stress.